Constitutionalizing Independence: Repositioning Consumer Protection Agencies as Independent State Auxiliary Bodies - Fitrah Bukhari; Anna Maria Tri Anggraini; Sri Bakti Yunari (Enrichment: Journal of Multidisciplinary Research and Development, 2026)
Consumer protection law enforcement in Indonesia has been stagnant for decades due to the institutional design of the National Consumer Protection Agency (BPKN), which is subordinate and only has consultative-passive authority. The unclear status of BPKN's independence under previous regulations has created legal uncertainty and weakened the legitimacy of the institution in relation to the executive branch and business actors. This article aims to analyze in depth the urgency of repositioning BPKN as an independent state auxiliary body by relying on the ratio decidendi of the Constitutional Court Decision Number 235/PUU-XXIII/2025. The research method used is normative legal research with a statute approach and a conceptual approach. The results of the study show that constitutional recognition of BPKN’s independence is an absolute requirement to ensure the effectiveness of market supervision, free from bureaucratic intervention. This structural repositioning must be accompanied by a transformation of functional authority through the provision of administrative adjudication mandates to provide coercive power for the protection of consumer rights. This article concludes that the transformation of BPKN into an independent state institution is a strategic step in strengthening Indonesia's constitutional architecture to realize economic justice and consumer sovereignty in the modern trade era